1995
DOI: 10.1207/s15327663jcp0402_04
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Subjective Knowledge, Objective Knowledge, and Usage Experience on Decision Making: An Exploratory Investigation

Abstract: Product knowledge has been recognized as an important factor in the research on consumer decision making. It has also been acknowledged that there are different types of knowledge. In this article, we examine the impact of three types of knowledge-subjective knowledge, objective knowledge, and usage experience-on selected aspects of consumer decision making. Effects are examined within the context of an electronic shopping scenario in which subjects selected a VCR brand based on brand and attribute information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
269
2
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(302 citation statements)
references
References 23 publications
15
269
2
6
Order By: Relevance
“…Naturally occurring correlations between subjective and objective knowledge poses a problem with separating the effect of each knowledge type if both are included in a model (Raju et al, 1995). In addition, the moderator effect of subjective knowledge on its consequences is difficult to isolate with the ones of other constructs which it relates, such as accessibility or certainty because both subjective knowledge and these related constructs are all consequences of objective knowledge (Smith et al, 2008).…”
Section: Consumer Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring correlations between subjective and objective knowledge poses a problem with separating the effect of each knowledge type if both are included in a model (Raju et al, 1995). In addition, the moderator effect of subjective knowledge on its consequences is difficult to isolate with the ones of other constructs which it relates, such as accessibility or certainty because both subjective knowledge and these related constructs are all consequences of objective knowledge (Smith et al, 2008).…”
Section: Consumer Knowledgementioning
confidence: 99%
“…For example, Raju et al (1995) suggest that knowledge types could be manipulated orthogonally to assess their independent effects. Such manipulations may allow a more precise study of the two-way and three-way interaction between other moderator variables as well.…”
Section: Conclusion Practical Implications and Limitationsmentioning
confidence: 99%
“…Each of these types of knowledge influences behaviour in a distinct way. Studies suggest that there is an interplay between subjective knowledge and information search (Brucks 1985, Moorman et al 2004, Raju et al 1995, risk taking (Kwon andLee 2009, Wang 2009), and practical financial decisions (Hadar et al 2013, Robb andWoodyard 2011). Sometimes, the influence of perceived knowledge on behaviour is even stronger than that of factual knowledge (Ellen 1994, Robb andWoodyard 2011).…”
mentioning
confidence: 99%
“…Past research has demonstrated that objective knowledge and subjective knowledge (i) are distinct constructs with unique measures (Brucks 1985;Park, Mothersbaugh, and Feick 1994), (ii) influence search and choice behavior differently (e.g., Radecki and Jaccard 1995;Raju, Lonial, and Mangold 1995), (iii) have unique antecedents (Park et al 1994;Radecki and Jaccard 1995), and (iv) have widely varying correlations (Brucks 1985 [0.54];Ellen 1994 [0.08]; Park et al 1994 [0.65]; Radecki and Jaccard 1995 [0.05]). This article focuses on subjective knowledge.…”
mentioning
confidence: 99%